Investigation of traffic safety and stability through simulation and theoretical modelling - Dong, Tianyu (Nanyang Technological University, 2023)
Traffic safety attracts increasing attention from both academia and industry, because road accident is one of the significant factors leading to death or injuries for human beings. In order to reduce traffic accidents caused by human-related errors, numerous countries and governments devoted efforts to developing more effective traffic policies and regulations. It is necessary to conduct multi-angle traffic safety analysis in various scenarios. In-depth and comprehensive analyses of traffic safety have the potential to assess the safety level, and figure out the essential factors leading to accidents, thereby providing useful guidance to mitigate the occurrence of accidents.